2013
DOI: 10.1007/s00404-013-2986-6
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of immigrant women of Turkish, Middle Eastern and North African origin in Berlin, Germany: a comparison of two time periods

Abstract: The perinatal health measures of women of Turkish origin have improved over time. The lower utilization rates of antenatal health care could be the expression of barriers to access the health care for pregnant women with migration background as offered in Germany. A risk group which needs a special focus by health care providers are women without a partner, irrespective of their origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
1
9
0
8
Order By: Relevance
“…The utilization of GPs and paediatricians was assessed by five studies showing small differences between PMB and the non-migrant population (NMP) [ 22 26 ]. The largest number of studies ( n = 14) was found for specialist consultations [ 22 , 23 , 25 36 ]. The majority of the results showed lower utilization for PMB, especially among 1st generation migrants.…”
Section: Resultsmentioning
confidence: 99%
“…The utilization of GPs and paediatricians was assessed by five studies showing small differences between PMB and the non-migrant population (NMP) [ 22 26 ]. The largest number of studies ( n = 14) was found for specialist consultations [ 22 , 23 , 25 36 ]. The majority of the results showed lower utilization for PMB, especially among 1st generation migrants.…”
Section: Resultsmentioning
confidence: 99%
“…Arbeiten einer Berliner Arbeitsgruppe zum Thema Schwangerschaft und Migration zeigen erfreulicherweise einen positiven Trend in den letzten Jahrzehnten: In den Jahren 1993-1997 als auch 2003-2007 zeigten sich sowohl hinsichtlich des Zeitpunktes der ersten Vorsorgeuntersuchung als auch der Anzahl der Untersuchungen hochsignifikante Unterschiede zwischen türkischen und deutschen Schwangeren, wobei die Häufigkeiten sowohl der späten Erstvorstellung als auch der geringeren Anzahl der Vorsorgeuntersuchungen im Zeitraum 2003-2007 abnahm [7]. Nach aktuellen Analysen nehmen Frauen mit Migrationshintergrund die Vorsorgeuntersuchungen während der Schwangerschaft in annähernd gleichem Ausmaß in Anspruch wie Frauen ohne Migrationshintergrund.…”
Section: Schwangerschaftsvorsorge Bei Patientinnen Mit Migrationshintunclassified
“…Generation 11,4 %, 2./3. Generation 11,9 % versus 5,3 % ohne Migrationshintergrund) [7,12]. Postpartal zeigen sich keine signifikanten Unterschiede bei den mittleren Hb-Werten, Frauen mit Migrationshintergrund der 2./3.…”
Section: Prä-und Postpartale Anämieunclassified
See 2 more Smart Citations